Modelling health impacts of hepatitis – model selection and treatment plans. Issue 1 (31st December 2022) - Reisch, Cordula
ABSTRACT: Hepatitis B and C are viruses causing liver infections and resulting in grave secondary diseases. While there are different treatments for chronic liver infections, the process of evolving chronic diseases is still not fully understood. This paper presents an economic-inspired model for the overall health of an infected organism. The health model is based on the results of a reaction diffusion model for describing the space-dependent dynamics of virus and T cells during a liver infection. The different treatments affect the parameters of the reaction diffusion model and influence therefore the well-being of the infected person during an infection. The health model is selected in a detailed process out of a class of possible models. The presented work provides a foundation for an optimal control problem for finding the best treatment strategy.